Smart City and Metropolitan Area: the Energy Component in the Case Studies of Genoa and Naples - Battarra, Rosaria; Lombardi, Chiara; Raimondo, Marco (TeMA - Journal of Land Use, Mobility and Environment, 2015)
The Smart City model is now considered one of the opportunities to rethink cities and, in general, the development of urban communities. One of the most relevant themes in the application of the Smart City paradigm is the city/energy relationship and Italian cities are fielding several actions to effectively cope with the energy issues. Nevertheless, actions and projects are often uncritically promoted as ‘smart’, but actually lack innovative contents and methods. Therefore, the aim of this research, of which we present the first findings, is the drafting of a survey, tested through field analysis, of the experimentations of Italian metropolitan areas on the Smart City topic. The in-depth analysis of two case studies, Genoa and Naples, allowed us to compare the actual state of the two cities. We have that they have undertaken a common path in the implementation of strategies to try to transform themselves into Smart Cities, focusing especially on the energy aspects.